2022
DOI: 10.1039/d2cc00570k
|View full text |Cite
|
Sign up to set email alerts
|

Copper(ii)-photocatalyzed decarboxylative oxygenation of carboxylic acids

Abstract: Showcasing the concept of light-induced homo¬lysis for the generation of radicals, the CuII-photocatalyzed decarboxylative oxygenation of carboxylic acids with molecular oxygen as the terminal oxidant is described. Two CuII-carboxylate complexes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Unlike the ring-opening reaction mechanism which was described above, primary and secondary carboxylic acids underwent iron photoinduced oxidative decarboxylation to generate the corresponding aldehydes and ketones in excellent to moderate yields ( 4a–4i ). 18 Several biologically and medicinally relevant molecules, such as isoxepac ( 3c ), indomethacin ( 3d ), and Ioxoprofen ( 3e ), were all suitable for oxidative decarboxylation and gave products 4c–4e in good yields. As representatives of acyclic tertiary carboxylic acids, compounds 3j and 3k were further subjected to the reaction conditions, and it was found that acetophenone ( 4j ) and benzophenone ( 4k ) were obtained as major products.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the ring-opening reaction mechanism which was described above, primary and secondary carboxylic acids underwent iron photoinduced oxidative decarboxylation to generate the corresponding aldehydes and ketones in excellent to moderate yields ( 4a–4i ). 18 Several biologically and medicinally relevant molecules, such as isoxepac ( 3c ), indomethacin ( 3d ), and Ioxoprofen ( 3e ), were all suitable for oxidative decarboxylation and gave products 4c–4e in good yields. As representatives of acyclic tertiary carboxylic acids, compounds 3j and 3k were further subjected to the reaction conditions, and it was found that acetophenone ( 4j ) and benzophenone ( 4k ) were obtained as major products.…”
Section: Resultsmentioning
confidence: 99%
“…In 2022 Reiser, Rehbein and Castellano reported the decarboxylative synthesis of ketones and aldehydes (Scheme 12). [92] In this catalytic method oxygen is used as terminal oxidant, which traps carbon radical intermediates and allows turnover via the formation of Cu‐alkylperoxo species. The substrates employed are mainly benzylic, although they report two examples of cyclic secondary alkyl showing that this protocol can be extended to this class of inactivated substrates.…”
Section: Synthetic Uses Of Lmct Reactivity In Organic Synthesismentioning
confidence: 99%
“…In a follow-up paper from the same group, Reiser and coworkers demonstrated a LMCT-triggered visible-light-induced decarboxylative oxygenation with 19 examples, including several with quantitative yields (Figure 8e). 82 They also studied the two possible Cu II intermediates, dinuclear paddle-wheel type Cu II -caboxylates and monodentate Cu II -carboxylates, in which they were able to conclude that the reactive intermediates for the photocatalytic decarboxylation are the monodentate Cu II -carboxylates.…”
mentioning
confidence: 99%
“…Copyright 2020 the American Chemical Society 81. (e) Schematic of the LMCT-triggered visible-light-induced decarboxylative oxygenation 82.…”
mentioning
confidence: 99%